Distinct regulatory pathways contribute to dynamic CHH methylation patterns in transposable elements throughout Arabidopsis embryogenesis - Lee, Jaehoon; Lee, Seunga; Park, Kyunghyuk; Shin, Sang-Yoon; Frost, Jennifer M.; Hsieh, Ping-Hung; Shin, Chanseok; Fischer, Robert L.; Hsieh, Tzung-Fu; Choi, Yeonhee (Frontiers in Plant Science, 2023)
CHH methylation (mCHH) increases gradually during embryogenesis across dicotyledonous plants, indicating conserved mechanisms of targeting and conferral. The biological function and epigenetic pathways underlying this process remain unclear, though it is suggested to enhance transposable element silencing. In Arabidopsis, mCHH is regulated by both small RNA-dependent DNA methylation (RdDM) and RNA-independent Chromomethylase 2 (CMT2) pathways. Here, we conducted DNA methylome profiling at five stages of Arabidopsis embryogenesis, and classified mCHH regions into groups based on their dependency on different methylation pathways. Our analysis reveals that the gradual increase in mCHH in embryos coincides with the expansion of small RNA expression and regional mCHH spreading to nearby sites at numerous loci. We identify distinct methylation dynamics in different groups of mCHH targets, which vary according to transposon length, location, and cytosine frequency. Finally, we highlight the characteristics of transposable element loci that are targeted by different mCHH machinery, showing that short, heterochromatic TEs with lower mCHG levels are enriched in loci that switch from CMT2 regulation in leaves, to RdDM regulation during embryogenesis